2020
DOI: 10.1111/apt.15817
|View full text |Cite
|
Sign up to set email alerts
|

Letter: does vitamin D have a potential role against COVID‐19? Authors' reply

Abstract: Editors,We thank Kumar et al for their comments on our review article and the letter connected with that by Panarese and Shahini. 1,2 We agree that there is a complicated effect of vitamin D in preventing the severity of COVID-19, while this mechanism is not exactly the same as that of influenza.Vascular injuries have become a focus of attention in COVID-19, especially in its severity and mortality; major risk factors include hypertension, diabetes and age. ACE2 is widely expressed in arterial and venous endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Publishing dates ranged from April 9 to May 20, 2020. Characteristics of enrolled studies 8,16,[19][20][21][22] are demonstrated in Table 1.…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%
“…Publishing dates ranged from April 9 to May 20, 2020. Characteristics of enrolled studies 8,16,[19][20][21][22] are demonstrated in Table 1.…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%
“…Additional authors recommend vitamin D supplements to boost the immune systems of patients diagnosed with COVID-19 (2 p , 35, 69, 71, 74, 75, 118, 120, 125, 230-233). However, most authors recommend widespread daily vitamin D supplementation (most often with 1,000-5,000 IU per day) to prevent and decrease the severity of COVID-19, at least until the pandemic abates (1,5,12,28,34,36,42,64,65,107,109,113,114,116,121,124,127,165,171,172,178,190,192,197,198,210,214,219,222,(234)(235)(236)(237)(238)(239)(240)(241)(242)(243)(244)(245)(246)(247)(248) (Figure 8).…”
Section: Covid-19-specific Recommendations Of Expertsmentioning
confidence: 99%
“…Another source of concern is an early systemic review and meta-analyses of 7 articles (that were published between 9th April and 20th May 2020), which reported that 25(OH)D levels were significantly lower for those with “poor” ( n = 634) than “good” ( n = 669) COVID-19 prognosis ( 236 ). Meta-analyses reported in this study are likely flawed with the inclusion of: studies previously in preprint, now seemingly withdrawn [e.g., Alipio et al, 2020, ( 236 )]; data from a letter, which does not cite any original findings ( 237 ); and, the inclusion of retrospective studies with small sample sizes that did not adjust for gender, age, comorbidities and other important factors [e.g., ( 209 , 213 ) of Table 1B].…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%